2015
DOI: 10.1080/2162402x.2015.1008342
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of tolerogenic human 6-sulfo LacNAc dendritic cells in renal cell carcinoma is associated with poor prognosis

Abstract: Dendritic cells (DCs) essentially contribute to the induction and regulation of innate and adaptive immunity. Based on these important properties, DCs may profoundly influence tumor progression in patients. However, little is known about the role of distinct human DC subsets in primary tumors and their impact on clinical outcome. In the present study, we investigated the characteristics of human 6-sulfo LacNAc (slan) DCs in clear cell renal cell carcinoma (ccRCC). slanDCs have been shown to display various tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 53 publications
0
19
1
Order By: Relevance
“…Thus, it has been demonstrated that Slan-DCs are numerous in metastatic tumor-draining lymph nodes from carcinoma patients, and that Slan-DCs accumulate in renal carcinoma. 13,14 Here, we show that the number of Slan-DCs is decreased in the PB of MM patients as compared to healthy donors and to MGUS patients. Moreover, we observed that the number of Slan-DCs increases with tumor load, suggesting that these cells can play a role in MM pathophysiology.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Thus, it has been demonstrated that Slan-DCs are numerous in metastatic tumor-draining lymph nodes from carcinoma patients, and that Slan-DCs accumulate in renal carcinoma. 13,14 Here, we show that the number of Slan-DCs is decreased in the PB of MM patients as compared to healthy donors and to MGUS patients. Moreover, we observed that the number of Slan-DCs increases with tumor load, suggesting that these cells can play a role in MM pathophysiology.…”
Section: Discussionmentioning
confidence: 61%
“…For instance, in renal cancer, their phenotype is impacted by the neoplastic cells which make them tolerogenic. 13 In contrast, in colon carcinoma, the contingent of circulating Slan-DCs remains normal as well as their inflammatory properties. 14 Moreover, Slan-DCs exhibit a remarkable plasticity in terms of phenotype which may depend on the local tissue they infiltrate.…”
Section: Introductionmentioning
confidence: 99%
“…SlanMo were shown in vitro to differentiate into proinflammatory DCs (13,15,69) or macrophages (14) depending on the local microenvironment. Similarly, in vivo slanMo were identified as IL-23-producing inflammatory dermal DCs in psoriasis (16), as DCs in tonsils (14), or as immature IL-10-producing macrophage-like cells in renal cell carcinoma (70).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a role for slan + cells was found in lupus skin lesions as well as in several other organs or diseases such as in multiple sclerosis, Crohn’s disease, rheumatoid arthritis, or HIV ( 16 20 ). Although slan + cells can clearly function as DCs, they may also differentiate into macrophages, as demonstrated in renal cell carcinoma ( 17 , 19 ).…”
Section: Introductionmentioning
confidence: 98%